OERaaS: Open Educational Resources as a Service With the Help of Virtual Containers - Corbi, Alberto; Burgos, Daniel (IEEE Latin America Transactions, 2017)
The new and challenging virtual containers are wide spread in a variety of sectors like systems administration, application deployment and service provision. However, these tools are not that much used in education and training, either in face-to-face or online forms. In this paper we show a technological set based on these containers and we discuss about a potential role in academic settings as a support to Open Educational Resources (OER). Furthermore, we present a very specific case study carried out with freshman students of the Bachelor of Science in Computer Science. These online students concentrate on a STEM subject, which stands for Science, Technology, Engineering and Maths. The promising results out of the tool evaluation might be migrated to other subjects, academic fields and educational levels. Likewise, we present already existing repositories of containers and discuss how good they are as a distribution service of OERs
Keywords: virtual containers; education; STEM; open educational resources; distribution platform; JCR; Scopus